Case report: Successful treatment with tofacitinib and colchicine in a patient with Schnitzler syndrome. (19th October 2022) - Li, Man; Chen, Yu‐Wen; Shen, Amy; Xie, Yong‐Xin; Wu, Yonglan; Zeng, Xianlin; Leong, Pui‐Ying
Abstract: We report a case of late‐onset Schnitzler syndrome successfully treated with Janus‐activated kinase (JAK) inhibitors and colchicine. Schnitzler syndrome should be considered for recurrent chronic urticaria when accompanied by fever, fatigue, rapid weight loss, and poor response to antihistamine treatment. Skin biopsy, bone marrow biopsy, and electrophoresis help confirm the diagnosis. Early diagnosis and treatment can lead to complete resolution of symptoms. Besides interleukin (IL)‐1 and IL‐6 inhibitors, JAK inhibitors and colchicine may be considered as other choices of treatment.